PENGARUH INVESTASI PMA DAN KREDIT PERBANKAN SEKTOR PERTANIAN TERHADAP PENYERAPAN TENAGA KERJA DAN PDRB SEKTOR PERTANIAN DI PROVINSI KALIMANTAN BARAT - B61112040, JAYUSMAN (Jurnal Ekonomi Daerah (JEDA), 2019)
This research entitled "The Influence of Foreign Investment and Credit of Agriculture Sector Banking on Manpower Absorption and Agriculture Sector GRDP in West Kalimantan Province". The purpose of this research is to know the influence of independent variable that is foreign investment and banking credit of agricultural sector to intervening variable that is labor absorption and dependent variable that is agriculture sector GRDP in West Kalimantan Province 1987-2016. The type of data used in this study is secondary data that is foreign investment, bank credit, employment absorption and GRDP of agriculture sector in West Kalimantan Province. Analyzer used in this research is path analysis. Basically the path analysis here is the merging of two structured regression equations. The result of the research shows that foreign investmentÂ  has significant effect on labor absorption, bank credit has no significant effect on the absorption of labor of agriculture sector, foreign investment and bank credit have significant effect to the GRDP of agricultural sector, and the absorption of labor has no significant effect on GDRP of agriculture sector.Keywords: foreign investment, bank credit, employment absorption, GRDP.